PENGARUH REPUTASI, DAN ELEKTRONIC WORD OF MOUTH TERHADAP KEPERCAYAAN PELANGGAN SHOPEE - Rizki Ramadani; Khairul Bahrun (Yayasan Insani Mandiri Santani, 2025)
The objective of this research is to determine the influence of reputation and electronic word of mouth on consumer trust among Shopee customers among Management Students at the Faculty of Economics and Business, Muhammadiyah University of Bengkulu. The population used in this research consists of 120 Management Students at the Faculty of Economics and Business, Muhammadiyah University of Bengkulu. The sampling technique used was purposeful sampling based on established criteria, involving 120 respondents. Data collection techniques included observation, documentation, and questionnaires. The processed data were analyzed using SPSS 24 formulas. Based on the research results and analysis of the influence of the variables Reputation and Electronic Word of Mouth on Customer Trust in Shopee Customers among Management Program Students at the Faculty of Economics and Business, Muhammadiyah University of Bengkulu, the following conclusions can be drawn: Reputation has a positive and significant effect on Customer Trust among Shopee customers among Management Program students at the Faculty of Economics and Business, Muhammadiyah University of Bengkulu. Keywords: Reputation, Electronic Word of Mouth, Consumer Trust